Evaluation of rutting potential of asphalts using resilient modulus test parameters. Issue 1 (2nd January 2019) - Radhakrishnan, Vishnu; Dudipala, Rajashekar Reddy; Maity, Anupam; Sudhakar Reddy, K.
Abstract : Rutting potential of asphalts can be evaluated in the laboratory by different tests. Any visco-elastic parameter of the mix evaluated at a high pavement temperature can be considered to be a possible parameter to distinguish mixes in terms of their rutting susceptibility. In this study, the potential of the time lag (between load and deformation) observed in a resilient modulus test as an appropriate parameter to explain the rutting resistance of different mixes has been examined. Resilient modulus is a parameter routinely evaluated by many agencies and is used as an input for design and evaluation of pavements. Time lag values were extracted from the resilient modulus test conducted at 35°C and 50°C on asphalt mixes prepared with (a) nine different types of binder and one aggregate gradation and (b) nine different aggregate gradations and with VG30 binder. A wheel tracking test was conducted on the mixes at 60°C. Time lag has been found to be sensitive to bitumen type and aggregate gradation. A strong correlation was observed between the time lag and rut depth measured in the wheel tracking test. It is evident from the present study that time lag measured from the resilient modulus test, which is conducted routinely by many agencies, has the potential to be used as a mix rutting parameter.